Highly Conductive Thin Uniform Gold‐Coated DNA Nanowires. Issue 26 (4th May 2018) - Stern, Avigail; Eidelshtein, Gennady; Zhuravel, Roman; Livshits, Gideon I.; Rotem, Dvir; Kotlyar, Alexander; Porath, Danny
Abstract: Over the past decades, DNA, the carrier of genetic information, has been used by researchers as a structural template material. Watson‐Crick base pairing enables the formation of complex 2D and 3D structures from DNA through self‐assembly. Various methods have been developed to functionalize these structures for numerous utilities. Metallization of DNA has attracted much attention as a means of forming conductive nanostructures. Nevertheless, most of the metallized DNA wires reported so far suffer from irregularity and lack of end‐to‐end electrical connectivity. An effective technique for formation of thin gold‐coated DNA wires that overcomes these drawbacks is developed and presented here. A conductive atomic force microscopy setup, which is suitable for measuring tens to thousands of nanometer long molecules and wires, is used to characterize these DNA‐based nanowires. The wires reported here are the narrowest gold‐coated DNA wires that display long‐range conductivity. The measurements presented show that the conductivity is limited by defects, and that thicker gold coating reduces the number of defects and increases the conductive length. This preparation method enables the formation of molecular wires with dimensions and uniformity that are much more suitable for DNA‐based molecular electronics. Abstract : Conductive metallized DNA wires merge advantageous DNA properties, such as its ability to self‐assemble, with the high conductivity and stability of the metal coating. An improved method for uniformly coating DNA with a continuous gold layer is presented, achieving very thin conducting wires. Detailed conductivity measurements show the importance of defects in limiting the conductive length of these wires.